Financial incentives to Medicaid smokers for engaging tobacco quit line treatment: maximising return on investment. Issue 3 (30th May 2019) - Mundt, Marlon P; Baker, Timothy B; Piper, Megan E; Smith, Stevens S; Fraser, David L; Fiore, Michael C
Abstract : Background: Low-income smokers experience greater difficulty in quitting smoking than do other smokers. Providing financial incentives for treatment engagement increases smoking cessation success. This study models the cost-effectiveness of varying levels of financial incentives to maximise return on investment (ROI) for engaging low-income Medicaid recipients who smoke to take calls from a tobacco quit line. Methods: Participants (N=1900) were recruited from May 2013 to June 2015 through quit line-based (n=980), clinic-based (n=444) or community-based referrals (n=476) into the Wisconsin Medicaid Quit Line Incentive project. Incentive (n=948) and control group participants (n=952) received 30 versus 0 per call, respectively, for taking up to five Wisconsin Tobacco Quit Line (WTQL) calls. Cost-effectiveness analyses estimated the incremental cost-effectiveness ratio for alternative financial incentives for engagement with WTQL calls. Probabilistic sensitivity analysis was employed to determine an optimal strategy for financial incentives to minimise the cost per individual who quit smoking. Results: Using fixed payments, the incremental cost-effectiveness ratio of 2316 per smoker who quit in the randomised trial decreased to 2150 per smoker who quit when the incentives were modelled at 20 per each of five WTQL calls taken. Using variable payments, the minimal cost per additional smoker who quit was 2125 when incentives for the first four WTQL calls were set at 20, and the financial payment for the fifth WTQL call was set at 70. Conclusions: Modelling suggests that financial incentives in the amount of 20 per call for taking the first four quit line calls and 70 for taking a fifth quit line call maximise ROI to engage low-income smokers with evidence-based smoking cessation treatment.